My Math Forum Equations with Roots and Exponents

 Algebra Pre-Algebra and Basic Algebra Math Forum

 January 7th, 2019, 02:31 AM #1 Newbie   Joined: Oct 2018 From: arizona Posts: 6 Thanks: 0 Equations with Roots and Exponents I'm struggling with the equation below. I've tried putting it into quadratics form to use the quadratics formula, but it has been too computationally arduous for me. I'm not sure where else to start. $x^2+m^2=2mx+(nx)^2$ Since I'm posting making this post, I may as well ask for help on another problem, which is $\sqrt{x^2+3x+7}-\sqrt{x^2-3x+9}+2=0$ I've tried isolating one of the roots on the left side and squaring both sides, but that has not worked. I've tried squaring both sides initially, and so far that has not worked (I end up with $50x^2-12x+130$ doing this, somehow). I've tried representing the roots as terms with fractional exponents, and no luck there either. I must be misusing arithmetic properties or something. Note: for both equations, the goal is to find all real solutions. Complex solutions are to be excluded.
January 7th, 2019, 04:20 AM   #2
Global Moderator

Joined: Oct 2008
From: London, Ontario, Canada - The Forest City

Posts: 7,968
Thanks: 1152

Math Focus: Elementary mathematics and beyond
Quote:
 Originally Posted by sigma $\sqrt{x^2+3x+7}-\sqrt{x^2-3x+9}+2=0$
Some work:

$\displaystyle a=x^2-3x+9,\quad b=x^2+3x+7$

$\displaystyle 2=\sqrt a-\sqrt b$

$\displaystyle 2\sqrt{ab}=(a+b)-4$

$\displaystyle 0=(a-b)^2-8(a+b)+16$

$\displaystyle 0=5x^2-6x-27$

I leave it to you to fill in and finish up.

 January 7th, 2019, 05:08 AM #3 Newbie   Joined: Oct 2018 From: arizona Posts: 6 Thanks: 0 Why is the equality equal to 2 in the beginning? Shouldn't it be -2 since we would have to subtract it to get it on the other side? I don't understand the third line of reasoning that is \displaystyle 2\sqrt{ab}=(a+b)-4 However, I did work with the polynomial in the end and got the same answer my textbook got, so I know you're right. I just don't understand why you're right.
January 7th, 2019, 05:20 AM   #4
Math Team

Joined: Oct 2011

Posts: 14,597
Thanks: 1039

Quote:
 Originally Posted by sigma I'm struggling with the equation below. I've tried putting it into quadratics form to use the quadratics formula, but it has been too computationally arduous for me. I'm not sure where else to start. $x^2+m^2=2mx+(nx)^2$
n^2(x^2) - x^2 + 2mx - m^2 = 0

(n^2 - 1)x^2 + 2mx - m^2 = 0

So: a = n^2 - 1, b = 2m, c = -m^2

Finish it.....and happy new year!

January 7th, 2019, 05:49 AM   #5
Math Team

Joined: Oct 2011

Posts: 14,597
Thanks: 1039

Quote:
 Originally Posted by sigma Why is the equality equal to 2 in the beginning?
Look CAREFULLY at Greg's substitution to a and b:

sqrt(b) - sqrt(a) + 2 = 0

so: 2 = sqrt(a) - sqrt(b)

You're spending too much time on your iPhone

 January 7th, 2019, 08:26 AM #6 Global Moderator   Joined: Dec 2006 Posts: 21,036 Thanks: 2273 (nx)² - (x - m)² = 0 $\implies$ (nx - x + m)(nx + x - m) = 0 (n² - 1)x² + 2mx - m² ≡ ((n - 1)x + m)((n + 1)x - m) Thanks from topsquark
 January 7th, 2019, 09:23 AM #7 Math Team   Joined: Dec 2013 From: Colombia Posts: 7,691 Thanks: 2670 Math Focus: Mainly analysis and algebra An alternative approach to greg1313's: \begin{align} \sqrt{x^2+3x+7} - \sqrt{x^2-3x+9} + 2 &= 0 \\ \sqrt{x^2-3x+9} - \sqrt{x^2+3x+7} &= 2 &\text{(Eqn 1)} \\ (x^2 - 3x + 9) - (x^2 + 3x + 7) &= 2\sqrt{x^2 + 3x + 7} + 2\sqrt{x^2 - 3x + 9} &\text{(Eqn 2)} \\ 2-6x &= 2\sqrt{x^2 + 3x + 7} + 2\sqrt{x^2 - 3x + 9} \\ 1-3x &= \sqrt{x^2 + 3x + 7} + \sqrt{x^2 - 3x + 9} &\text{(Eqn 3)} \\ \text{(Eqn 1)} + \text{(Eqn 3)} \implies 2\sqrt{x^2 - 3x + 9} &= 3 - 3x \\ 4(x^2 - 3x + 9) &= 9 - 18x + 9x^2 \\ 5x^2 - 6x - 27 &= 0 \\ \tfrac15\big((5x)^2 - 6(5x) - 135\big) &= 0 \\ \tfrac15\big((5x)-15\big)\big((5x) + 9\big) &= 0 \\ (x-3)(5x+9) &= 0 \end{align} For $\text{(Eqn 2)}$ we multiplied by $\big( \sqrt{x^2 + 3x + 7} + \sqrt{x^2 - 3x + 9} \big)$ using the identity $$a^2 - b^2 = (a-b)(a+b)$$ This has the advantage that we only square the once. Each time we square the equation there is a risk that we add solutions that may not satisfy the original equation, so we have to validate every solution that we obtain: $$\sqrt{3^2+3\times 3 + 7}-\sqrt{3^2 - 3\times 3 + 9} = \sqrt{25} - \sqrt{9} = 5 - 3 = 2$$ So $x=3$ is not a solution. Thanks from topsquark and ProofOfALifetime Last edited by v8archie; January 7th, 2019 at 09:42 AM.

 Thread Tools Display Modes Linear Mode

 Similar Threads Thread Thread Starter Forum Replies Last Post jiasyuen Algebra 3 May 22nd, 2015 06:31 AM oshmunnies Algebra 12 August 13th, 2013 12:26 PM tsa256 Algebra 2 July 30th, 2010 01:00 PM ali987 Linear Algebra 0 July 11th, 2010 10:42 PM Mr_Quick Algebra 2 May 7th, 2009 05:32 AM

 Contact - Home - Forums - Cryptocurrency Forum - Top